Homeless in the hospital: A call to strengthen multidisciplinary care for children awaiting out-of-home and psychiatric placements - Aysha Jawed; Aysha Jawed; Rachel Boro-Hernandez; Rachel Boro-Hernandez; Diane Pickett; Diane Pickett (Frontiers in Pediatrics, 2023)
Increasingly more school-age and adolescent children continue to await psychiatric or out-of-home placements across pediatric healthcare systems. These children comprise the growing overstay pediatric population. The medical, developmental, socioemotional, behavioral and academic needs of these patients are complex and diverse. The uncertainty of waiting times for placement further continues. This growing pediatric issue emphasizes the importance of mobilizing a myriad of resources across healthcare and community contexts to support these patients during this precarious time. The reality is that there is a significant scarcity of placement resources which contributes to extended waiting times for placement. This contemporary issue brings child development, ethical and moral considerations, and healthcare operations to the forefront. We discuss a myriad of dimensions surrounding this growing issue from our clinical practice. We present a wealth of recommendations in working through each of these dimensions through a multi-systems approach that include development of individualized care plan, access to consistent psychiatric services, and implementing short-term and long-term goals pertaining to treatment and placement. We also review our clinical practices that have supported these patients on a continuum at our healthcare institution which integrate our recommendations and also involve an open line of communication with established community partners involved in the care of these children. Furthermore, we propose suggestions from an operational perspective on developing a comprehensive, multidisciplinary care model for this fragile and oftentimes neglected patient population across the healthcare system as the basis to achieve equity and translational impact in the quality and delivery of healthcare care services across pediatric healthcare systems.